Hirschsprung’s disease and associated syndrome and malformation -A report of four cases. (Indian Journal of Case Reports, 2022)
Background: Hirschsprung’s disease is a genetic disorder characterized by the absence of ganglion cells in different lengths of the intestine. It is one of the common causes of intestinal obstruction in neonates. Materials and Methods: The study was carried out from January 2017 to January 2020 in the Department of Pathology in a Tertiary care hospital. The biopsy specimens from spastic segment and colostomy or ileostomy sites were sent for evaluation of ganglion cells. Results: During carrying out the study we came across two cases of biopsy that proved Hirschsprung’s disease who manifested the various signs and symptoms associated with two different syndromes and one malformation and one associated neoplasm Conclusion: Two different syndromes and one associated malformation and neoplasm were detected in patients of Hirschsprung’s disease during a 3-year study. Keywords: Hirschsprung’s disease, ganglion cell, hypertrophic nerve fiber, malformation, neoplasm, syndrome.